Takhrij and Syarah Hadith of Agrotechnology Sabir Leaves as Eye Pain Medicine - Annisa Nur Azizah; Wahyudin Darmalaksana; Yati Setiati Rachmawati (UIN Sunan Gunung Djati Bandung, 2021)
This study aims to discuss the hadith with regard to agrotechnology. This research method is a qualitative type through literature study and field studies with the takhrij and sharah hadith approaches. The results and discussion of this study are about the content and benefits of sabir leaves as an eye pain medication recommended by the Prophet Muhammad. The conclusion of this research is takhrij and syarah hadith of the Prophet about the content of sabir leaves starting from overcoming panda eyes, minus eyes, and cataracts.